To Study Clinicopathological Spectrum of Ovarian Tumour and Tumour Like Lesions in a Tertiary Health Care Centre of North India - Surbhi Mahajan; Deepti Gupta; Aishvarya Jandial; Subhash Bhardwaj (Dr. Annil Mahajan, 2023)
Introduction: Variety of primary ovarian neoplasms reflects the complex function of the ovary. The study was conducted to know distribution of ovarian lesions, analyse their mode of presentation and distribution of various morphological pattern of ovarian neoplasms. Methods: A systematic search identified 205 ovarian lesion specimens submitted in the department over a time period of three years (January 2018- December 2020). The tumours were classified according to World Health Organization (WHO) classification 2016. Results: There was a wide age range from 11 years to 72 years. Among neoplastic ovarian lesions peak was seen in the fourth decade, mean 48.1 years. Sonographic appearance showed a prominent solid component (32/32,100%) in all malignant cases. Non-neoplastic cysts were more common (107, 52.2%) than neoplastic tumours (98, 47.8%). Among the neoplastic tumours (62) 63.3% were benign. Four borderline tumours (4.1%) were noted in the study. Surface epithelial tumours were the commonest histomorphological type 67 (68.4%). Granulosa cell tumour (4/32, 12.5%) was the commonest sex cord stromal tumour. Conclusion: Ovarian lesion possess wide gamut of histology. Non neoplastic ovarian lesions occur more frequently when compared to neoplastic lesions. Major proportion of malignant ovarian tumours was contributed by surface epithelial tumours.